Development of HPTLC analysis to evaluation of Rosmarinic and Caffeic acids in Salvia aegyptiaca extract and analysis of its antioxidant activities - Zahra Sabahi; Forough Karami; Fatemeh Farmani; Ali Hosseini; Mahmoudreza Moein (Shiraz University of Medical Sciences, 2023)
Phenolic acids such as rosmarinic acid (RA) and caffeic acid (CA), are the most significant phenolic compounds in Lamiaceae family, including Salvia species. The aim of this study was to evaluate the RA and CA contents of Salvia aegyptiaca (SA) methanol extract and its antioxidant activity. RA and CA analysis were performed by HPTLC-image analysis. UV-VIS spectrophotometry was used for the evaluation of the phenolic acid. The samples were spotted on a HPTLC plate silica gel. The toluene- ethyl acetate- formic acid was used as mobile phase. Plates were scanning at 366 nm and absorption mode was scanned. Finally, the image of plates was obtained by visualizer at 254 and 366 nm and visible wavelengths. This Method was then validated in terms of precision and accuracy at inter- day and intra-day. The extracts were screened to determine antioxidant activity using the DPPH radical scavenging assay, FRAP, ABTS, ORAC, Nitric oxide scavenging ability and cellular antioxidant activity. The RA and CA contents of extracts were 11.33±0.36 and 6.36±4.7 mg/g respectively. The SA were able to scavenge free radicals such as DPPH•, NO• and O2•-, and the ability to reduce Fe3+, as well. This activity highly associated with RA and CA contents. Developed HPTLC method is rapid, simple and reliable and it is suggested to use in routine assay of Salvia sp. extracts containing RA and CA which are a generally marker in various plant. Moreover, SA could be considered as natural source of antioxidants.